α-Synuclein-112 Impairs Synaptic Vesicle Recycling Consistent With Its Enhanced Membrane Binding Properties - Soll, Lindsey G.; Eisen, Julia N.; Vargas, Karina J.; Medeiros, Audrey T.; Hammar, Katherine M.; Morgan, Jennifer R. (Frontiers in Cell and Developmental Biology, 2020)
Synucleinopathies are neurological disorders associated with α-synuclein overexpression and aggregation. While it is well established that overexpression of wild type α-synuclein (α-syn-140) leads to cellular toxicity and neurodegeneration, much less is known about other naturally occurring α-synuclein splice isoforms. In this study we provide the first detailed examination of the synaptic effects caused by one of these splice isoforms, α-synuclein-112 (α-syn-112). α-Syn-112 is produced by an in-frame excision of exon 5, resulting in deletion of amino acids 103-130 in the C-terminal region. α-Syn-112 is upregulated in the substantia nigra, frontal cortex, and cerebellum of parkinsonian brains and is correlated with susceptibility to sporadic Parkinson’s disease (PD), dementia with Lewy bodies (DLB) and multiple systems atrophy (MSA). We report here that α-syn-112 binds strongly to anionic phospholipids when presented in highly curved liposomes, similar to α-syn-140. However, α-syn-112 bound significantly stronger to all phospholipids tested, including the phosphoinositides. α-Syn-112 also dimerized and trimerized on isolated synaptic membranes, while α-syn-140 remained largely monomeric. When introduced acutely to lamprey synapses, α-syn-112 robustly inhibited synaptic vesicle recycling. Interestingly, α-syn-112 produced effects on the plasma membrane and clathrin-mediated synaptic vesicle endocytosis that were phenotypically intermediate between those caused by monomeric and dimeric α-syn-140. These findings indicate that α-syn-112 exhibits enhanced phospholipid binding and oligomerization in vitro and consequently interferes with synaptic vesicle recycling in vivo in ways that are consistent with its biochemical properties. This study provides additional evidence suggesting that impaired vesicle endocytosis is a cellular target of excess α-synuclein and advances our understanding of potential mechanisms underlying disease pathogenesis in the synucleinopathies.